The NURBS Book - Piegl, Les (Monographs in visual communication., 1997)
The NURBS book covers all aspects of non-uniform rational B-splines necessary to design geometry in a computer aided environment. Basic B-spline features, curve and surface algorithms, and state-of-the-art geometry tools are all discussed. Detailed code for design algorithms and computational tricks are covered too, in a lucid, easy-to-understand style, with a minimum of mathematics and using numerous worked examples. The book is a must for students, researchers, and implementors whose work involves the use of splines. "Some years ago a few researchers joked about NURBS, saying that the acronym really stands for Nobody Understands Rational B-Splines write the authors in their foreword; they formulate the aim of changing NURBS to EURBS, that is, Everybody ... There is no doubt that they have achieved this goal. ... I highly recommend the book to anyone who is interested in a detailed description of NURBS. It is extremely helpful for students, teachers and designers of geometric modelling systems. ..."--H. Pottmann, Computer Aided Design, 1996.